Marketing Communication Strategy Pisau Cukur Merk Kingsman - Marya Mujayana (Fakultas Ekonomi Universitas PGRI Adi Buana, 2021)
This study aims to examine changes in the integrated marketing communication strategy for the KingsMan brand knife. This research focuses on the strategy changes made by KingsMan in market penetration in the midst of market competition. Apart from market competition. The product brand is constrained by restrictions during the pandemic, so a change in marketing strategy is needed. This research uses descriptive qualitative method with primary and secondary data. The results of the study show that changing KingsMan's strategy by using marketing mix techniques is able to increase product absorption in the market. In addition to increasing sales, KingsMan's marketing mix also increased brand awareness of the brand. This study has limitations in terms of the respondent's area in Surabaya and the digital marketing channel used. This study provides recommendations for further research that emphasizes aspects of digital marketing strategies